2003
DOI: 10.1021/jp035013o
|View full text |Cite
|
Sign up to set email alerts
|

Manipulations of the B-Side Charge-Separated States' Energetics in the Rhodobacter sphaeroides Reaction Center

Abstract: The mutation HL(M182) in the Rb. sphaeroides reaction center (RC) results in the replacement of the monomer bacteriochlorophyll on the inactive side (B side) of the reaction center with a bacteriopheophytin (φB). In φB containing reaction centers, excitation of the initial electron donor, the special pair P, results in about 35% electron transfer along the normally inactive B side. However, the electron is transferred only to the exchanged cofactor φB. Several additional mutations in close proximity to bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 44 publications
(133 reference statements)
6
46
0
Order By: Relevance
“…In recent years this asymmetric functionality has been broken via site-directed mutagenesis producing RCs that undergo B-side electron transfer to give either P + H B -or P + φ B -(where φ B denotes a bacteriopheophytin that replaces B B ) in yields as high as 35%. [5][6][7][8][9][10][11][12][13] Charge-separated states on the B-side of the RC also have been reported under conditions of high pulse energy or short wavelength excitation with native complexes. 14,15 Recently it was shown that P + H B -supports electron transfer to Q B , with the rate more than 10-fold slower than P + H A -f P + Q A -electron transfer.…”
Section: Introductionmentioning
confidence: 91%
“…In recent years this asymmetric functionality has been broken via site-directed mutagenesis producing RCs that undergo B-side electron transfer to give either P + H B -or P + φ B -(where φ B denotes a bacteriopheophytin that replaces B B ) in yields as high as 35%. [5][6][7][8][9][10][11][12][13] Charge-separated states on the B-side of the RC also have been reported under conditions of high pulse energy or short wavelength excitation with native complexes. 14,15 Recently it was shown that P + H B -supports electron transfer to Q B , with the rate more than 10-fold slower than P + H A -f P + Q A -electron transfer.…”
Section: Introductionmentioning
confidence: 91%
“…B), which mirrors the A‐side residue L104Glu known to form a hydrogen bond with H A . Previous work has shown that Asp or Glu substituted at M133/M131 can form a hydrogen bond with H B , promoting its reduction. The combination of the V(M131)E (‘E’) substitution with the ‘core’ FHV and YFHV mutations in the R. capsulatus RC has resulted in large increases in yields of B‐side ET .…”
Section: Rationale For Choice Of Substitutions Employedmentioning
confidence: 98%
“…[55][56][57] Additionally, calculations generally place the P + B -state higher in free energy than the P + H -state on both L and M branches by 0.15-0.25 eV, consistent with the difference in redox potentials of bacteriochlorophyll and bacteriopheophytin in vitro. [58][59][60][61] Calculations and experiments have provided estimates or bracketed ranges for the free energies of the charge-separated states in the wild-type RC: P + B L -0.05-0.1 eV below P*; 29,50,51,[62][63][64][65][66][67][68][69][70] P + H L -∼0.25 eV below P* when relaxed; [71][72][73][74][75] P + B M -0.1-0.2 eV above P* and P + H M -below P* by no more than ∼0.15 eV and probably within 0.1 eV. [50][51][52][76][77][78][79] Systematic efforts to manipulate the free energy differences of the L-and M-branch charge-separated states by site-directed mutagenesis of key amino acids, including those near B M and B L , have led to mutant RCs in which electron transfer to the M branch competes effectively with charge separation to the L branch, yielding P + H M -(reviewed in ref 80).…”
Section: Introductionmentioning
confidence: 99%